Oxygen-catalysed sequential singlet fission - Wollscheid, Nikolaus; Brosius, Victor; Bunz, Uwe H. F.; Motzkus, Marcus; Buckup, Tiago (Nature Communications, 2019)
Singlet fission is a promising carrier multiplication process, where a singlet exciton is split in two triplet states. Here the authors propose an oxygen-assisted two-step mechanism for singlet fission accounting for ~ 40% triplet quantum yield in dilute solutions where the single-step mechanism is inactive.
Gesehen am 13.03.2020